The Persistence of Shocks to Profitability - McGahan, Anita M.; Porter, Michael E. (The Review of Economics and Statistics, 1999)
In this study, we use data for 1981 through 1994 on a large sample of U.S. companies to examine the persistence of incremental industry, corporate-parent, and business-specific effects on profitability. Our results indicate that the incremental effects of industry on profitability persist longer than the incremental effects of the corporate parent and of the specific business. Changes in industry structure have a more persistent impact on profitability than do changes in firm structure.